PERLINDUNGAN MASYARAKAT TERHADAP ANAK PENDERITA HIV/AIDS DI KOTA SURAKARTA - Salsabila, Rara Nur; Fadhila, Melaila Nurul; Rahayu, Septi; Arini, Liss Dyah Dewi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The number of cases of neglect of children suffering from HIV / AIDS caused by lack of knowledge of HIV / AIDS transmission and cure is the background of the publication of this article with the aim of being able to add insight to families, communities, and the environment around the transmission of HIV / AIDS in children so as to reduce the level of neglect of children with HIV / AIDS. The research method used in this article is qualitative research with descriptive research through interviews and literature studies. The amount of neglect of children in the city of Surakarta is influenced by the factor of lack of education about HIV / AIDS so that there is a need for socialization and education about HIV / AIDS, especially in children so that sufferers can also live normally